Early Intervention in Psychosis: Effectiveness and Implementation of a Combined Exercise and Health Behavior Intervention Within Routine Care - Smith, Jo; Griffiths, Lisa A.; Band, Marie; Hird-Smith, Rachael; Williams, Briony; Bold, Justine; Bradley, Eleanor; Dilworth, Richard; Horne, Dominic (Frontiers in Endocrinology, 2020)
Aim: Young-people with psychosis have higher rates of obesity, premature cardiovascular disease and death compared to non-psychotic peers in the general population due to changes in metabolic regulation linked to antipsychotic medication and adverse health risk behaviors. The aim of this paper is to outline the development, implementation, and evaluation of a combined 12-week exercise and health behavior intervention delivered as part of an Early Intervention in Psychosis (EIP) routine service, within the UK. Methods: Participants (n=27) completed a 12-week combined intervention program, engaging in weekly, 90-minute sessions comprising a healthy behavior education session (45 minutes), followed by a facilitated exercise session (45 minutes). Anthropometric data from participants (n=26) were collected at baseline, 12 weeks, and 12 months post-intervention. Health behaviors and clinical measurements were assessed at baseline and 12 months. Results: Mean baseline data suggests participants were at an increased health risk on entry to the program, with elevated values in mean body mass index (BMI; 70% overweight/obese), waist circumference, resting heart rate, and triglycerides. Fifty percent reported smoking daily, 64% ate < 5 fruits/vegetables per day, and 52% of participants were prescribed highly obesogenic antipsychotic medications (i.e., Olanzapine). At 12 weeks and 12 months, no changes were observed in mean BMI, waist circumference or any other clinical variable (p > 0.05). At 12 months, participants reported a positive impact on health behaviors including improved diet, increased physical activity levels, and cessation of substance use (n=2), alcohol use (n=2), and smoking (n=4). Focus groups captured participant experiences, engagement with and satisfaction with the program, including challenges/barriers to program adherence. Conclusions: The 12-week exercise and health behaviors program supported participants to attenuate their physical health risk which was sustained at 12 months follow up. Self-reported positive health behavior changes are likely to have contributed to the prevention of excessive weight gain in this high-risk period. The evaluation was designed to have validity for a ’real world EIP setting’ and reflect the complexity of delivery amongst this participant group. Evaluation findings influenced subsequent commissioning of the physical health intervention as an ongoing element of routine EIP care within the participant site.